2015
DOI: 10.12806/v14/i2/r3
|View full text |Cite
|
Sign up to set email alerts
|

Walking the Razor’s Edge: Risks and Rewards for Students and Faculty adopting Case in Point Teaching and Learning Approaches

Abstract: Case in Point (CIP) is an interactive leadership development method pioneered by Ronald Heifetz. CIP instructors follow a fluid class structure, in which group dynamics and student concerns become catalysts for learning. CIP proponents defend the method's potential to help students experience real life leadership challenges. To date, however, very limited research exists on the effectiveness and risks of the CIP. This case study research explored the risks and rewards of CIP as experienced by a professor and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Moreover, even looking before the global impacts of the pandemic, in a 2017 publication by the Varkey Foundation, only about 30% of Gen Z reported having good overall emotional well‐being, and only 17% reported having good overall physical well‐being (Broadbent et al., 2017). Furthermore, this issue does not exist alone with Gen Z, as previous scholars have identified ambiguity and uncertainty as a source of risk and heat (Weng & Hubbard, 2022; Wildermuth et al., 2015).…”
Section: Discomfort In Emergent Pedagogiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, even looking before the global impacts of the pandemic, in a 2017 publication by the Varkey Foundation, only about 30% of Gen Z reported having good overall emotional well‐being, and only 17% reported having good overall physical well‐being (Broadbent et al., 2017). Furthermore, this issue does not exist alone with Gen Z, as previous scholars have identified ambiguity and uncertainty as a source of risk and heat (Weng & Hubbard, 2022; Wildermuth et al., 2015).…”
Section: Discomfort In Emergent Pedagogiesmentioning
confidence: 98%
“…In a space where heat comes first over positive student interaction, we may begin to receive more criticism, oftentimes by way of critiquing the method or choice of method, rather than praise or gratitude. This can be further complicated when using emergent pedagogy in educational or organizational contexts where there may be a lack of institutional support in the first place (Wildermuth et al., 2015). The lack of support at the organizational level further reduces the support instructors have in the delivery process.…”
Section: The Instructor and Heat: Wear And Tear Of The Cruciblementioning
confidence: 99%
See 1 more Smart Citation
“…There is limited empirical evidence demonstrating the benefit, effectiveness, or impact of the case-inpoint pedagogy for leadership development with the exception of descriptive texts published in the last two decades describing how organizations have used it (Green & McBride, 2015;Parks, 2005). Wildermuth et al (2015) examined the varied risks and rewards that students experienced when taking a course with case-in-point pedagogy but this research did not specifically examine the impact of the pedagogy on students. Haber-Curran et al's (2013) research on the experiences of undergraduates who took a course that partially utilized the pedagogy found in an analysis of students' course reflection papers that students' selfawareness increased and that they gained a broader view of leadership.…”
Section: Benefits and Effectiveness Of Case-in-pointmentioning
confidence: 99%
“…In other words, while empirical studies on the use of case-in-point have not explicitly examined CIP as a pedagogical practice, aspects of the pedagogy have been reported on that show changes in behaviors, and engagement. This research has suggested that additional skills could be developed and that it holds promise for supporting leadership development (Kniffin et al, 2017;Werner et al, 2016;Wildermuth et al, 2015).…”
Section: Benefits and Effectiveness Of Case-in-pointmentioning
confidence: 99%